Answer:
Yes, Tran is correct .
By substituting different values for x, we can see that
-7 +
+ 2x is equivalent to 4x-7.
Explanation:
Lets substitute x = 1 in
-7 +
+ 2x
⇒
-7 +
+ 2(1)
⇒
-7 +
+ 2
⇒ -3.
Now, substitute x = 1 in 4x-7.
⇒ 4(1) - 7 = -3.
⇒ we got -3 in both the cases.
Now let us substitute x = 2 in
-7 +
+ 2x
⇒
-7 +
+ 2(2).
⇒
- 7 +
+ 4.
⇒ 1.
now, x =2 in 4x -7.
⇒ 4(2) - 7 = 1.
⇒ we got 1 in both the cases.
Not only these values, for any value of x both the expressions give same value, because,
-7 +
+ 2x is equivalent to 4x-7.
-7 +
+ 2x
= -7 +
+ 2x
= -7 + 2x + 2x.
= 4x-7.